Patient‐controlled hospital admission: A novel concept in the treatment of severe eating disorders. Issue 7 (28th August 2015) - Strand, Mattias; Gustafsson, Sanna A.; Bulik, Cynthia M.; von Hausswolff‐Juhlin, Yvonne
<x xml:space="preserve">Abstract</x> © 2015 Wiley Periodicals, Inc. (Int J Eat Disord 2015; 48:842–844)